Antioxidative stress potential of Cinnamomum zeylanicum in humans: a comparative cross-sectional clinical study. Issue 1 (January 2006) - Ranjbar, Akram; Ghasmeinezhad, Sara; Zamani, Hosnieh; Malekirad, Ali Akbar; Baiaty, Akram; Mohammadirad, Azadeh; Abdollahi, Mohammad
Background: Cinnamomum zeylanicum is an important spice and aromatic crop used in folk medicine. Cinnamon is usually regarded as the bark of the C. zeylanicum tree.Objective: The objective of this study was to determine the antioxidative stress capacity of cinnamon in humans when administered in a regular and controlled manner.Methods: A total of 54 normal subjects were divided into three groups, receiving water, regular tea or cinnamon tea for 2 weeks. Blood samples were obtained before and after treatment and analyzed for lipid peroxidation levels, total antioxidant power and total thiol groups by standard methods.Results: The results indicated increased total antioxidant power and total thiols but a decrease in lipid peroxidation levels in individuals who received regular or cinnamon tea compared with controls. The extent of increase in total antioxidant power and decrease in lipid peroxidation levels were more evident in individuals who received cinnamon tea compared with those who received regular tea.Conclusion: Cinnamon has a marked antioxidant potential and may be beneficial in alleviating the complications of many illnesses related to oxidative stress in humans.